Shear-bond strength of different Self-Etching adhesive systems to dentin with or without laser irradiation before photopolymerization (A comparative Study) - Wiaam M.O. AL-Ashou; Rajaa Taher; Alaa H. Ali (Saudi Dental Journal)
This study aimed at comparing shear-bond strength (SBS) of different self-etching adhesive systems (Clearfil S3 Bond Plus, G-Premio BOND and IBond) to dentin without or with diode-laser irradiation before photo-polymerization and to determine the effect of storage and thermo-cycling on SBS of adhesive systems. Methods: The buccal surface of 84 extracted maxillary premolars was grounded to create flat surface. The specimens were allocated into 3 groups (n = 28) depending upon the adhesive systems, then each group was divided into two sub-group (I, II) (n = 14). After the placement of respective adhesive systems on the flat surface, adhesive system in group I was photo-polymerized immediately, while in group II, the adhesive systems were exposed to diode-laser before photo-polymerization. Composite cylinder (4 mm in diameter and 2 mm height) was built on the flat surface of each specimen. Then group I and II were divided into two sub-groups (n = 7) according to the storage time and thermo-cycling (1 day without thermo-cycling or 72 days with thermo-cycling) then all the specimens were stored in distilled water. The SBS was measured at the end of storage period. ANOVA, Duncan’s Multiple Range Test and independent t-test “P ≤ 0.05” were used for data analysis. Results: G-premio BOND showed the highest mean value of SBS followed by Clearfil S3 Bond plus without significant difference between them, while IBond revealed the least mean value. Laser irradiation had positive effect on the bond-strength of all tested adhesive systems. The results also showed that the storage with thermo-cycling had negative effect on the bond-strength in groups without laser irradiation for all tested adhesive systems, while for groups with laser irradiation, the reduction in the bond-strength of all tested adhesive systems was not significant. Conclusion: Diode-laser application prior to photo-polymerization of self-etch adhesive systems significantly increased the bond-strength to dentin and can increase the durability of composite adhesion.